2013
DOI: 10.1080/02640414.2013.812791
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and health-related changes associated with a 12-week self-guided exercise programme in overweight adults: a pilot study

Abstract: Over 12 weeks, supervised physical activity (PA) interventions have demonstrated improvements in morphological and health parameters, whereas community walking programmes have not. The present study piloted a self-guided programme for promoting PA and reducing sedentary behaviour in overweight individuals and measured its effect on a range of health outcomes. Six male and 16 female sedentary adults aged 48.5 ± 5.5 years with body mass index (BMI) 33.4 ± 6.3 kg m(-2) were assessed for anthropometric variables, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Increased physical activity in interventional studies may result in a variety of effects including, but not limited to, improved resting cerebrovascular reactivity to hypercapnia (Murrell et al, 2013), reduced arterial pressure (Vicente-Campos et al, 2012), lower total cholesterol and triglycerides (Vicente-Campos et al, 2012), lower BMI and blood pressure (Stewart et al, 2013), better glycemic control (Roberts et al, 2013), reduced chronic low-grade inflammation (Nimmo et al, 2013), increased growth factor levels (Cotman and Berchtold, 2002), better sleep (Dzierzewski et al, 2014), and greater brain neurogenesis (Cotman and Berchtold, 2002). Many of these effects relate to health factors that may modulate AD risk (Launer et al, 2000; Del Bo et al, 2009; Solomon et al, 2009; Lee et al, 2010; Matsuzaki et al, 2011; Piriz et al, 2011; Vargas et al, 2011; Crane et al, 2013; Tolppanen et al, 2013; Di Meco et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Increased physical activity in interventional studies may result in a variety of effects including, but not limited to, improved resting cerebrovascular reactivity to hypercapnia (Murrell et al, 2013), reduced arterial pressure (Vicente-Campos et al, 2012), lower total cholesterol and triglycerides (Vicente-Campos et al, 2012), lower BMI and blood pressure (Stewart et al, 2013), better glycemic control (Roberts et al, 2013), reduced chronic low-grade inflammation (Nimmo et al, 2013), increased growth factor levels (Cotman and Berchtold, 2002), better sleep (Dzierzewski et al, 2014), and greater brain neurogenesis (Cotman and Berchtold, 2002). Many of these effects relate to health factors that may modulate AD risk (Launer et al, 2000; Del Bo et al, 2009; Solomon et al, 2009; Lee et al, 2010; Matsuzaki et al, 2011; Piriz et al, 2011; Vargas et al, 2011; Crane et al, 2013; Tolppanen et al, 2013; Di Meco et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There have been similar reports about the positive effects of walking on fatigue levels in similar populations. 24,25 The reduction in arthritis pain, however, was unexpected. A recent meta-analysis reported that walking did not decrease knee or hip arthritis pain but did improve physical function.…”
Section: Resultsmentioning
confidence: 99%